The concept of the Global Hunger Index - von Grebmer, Klaus; Bernstein, Jill; Hossain, Naomi; Brown, Tracy; Prasai, Nilam; Yohannes, Yisehac; Patterson, Fraser; Sonntag, Andrea; Zimmerman, Sophia-Maria; Towey, Olive; Foley, Connell (International Food Policy Research Institute, 2017)
The Global Hunger Index (GHI) is a tool designed to comprehensively measure and track hunger at the global, regional, and national levels. The International Food Policy Research Institute (IFPRI) calculates GHI scores each year to assess progress and setbacks in combating hunger. The GHI is designed to raise awareness and understanding of the struggle against hunger, provide a means to compare the levels of hunger between countries and regions, and call attention to the areas of the world in greatest need of additional resources to eliminate hunger.